APLlKASI KALSIUM KLORIDA DAN ETHEPHON DALAM UPAYA PENINGKATAN KUALITAS BUAH NANAS (Ananas comosus (L) Merr) - Nungki Kusuma Astuti; Moch Dawam Maghfoer; Roedy Soelistyono (Research Center for Chemistry - LIPI, 2013)
The objective of research was to obtain the treatmenttime of CaCl2 applications, dosage of CaCl2 and ethephonapplications to improve the fruit quality of pineapple. Thisresearch used Split-Split Plot Design and each treatmentreplicated 3times. The main plot is time ofCaCl2 applicationsthat consists of three levels, those are 90 day after flowering(daf), 120 daf and twice of CaCl2 applications at 90 and 120daf The sub plot is dosage of CaCl2 that consists of threelevels, those are 50 kg ha', 75 kg ha' and 100 kg ha', The subsub plot is dosage of ethephon that consists of two levels,those areO L ha' and 2,5 L ha', The results showed that thecombined treatment ofCaCl2 application on 90 daf, dosage ofCaCl250 kg ha' and dosage of ethephon 2.5 L ha' producedistribution external fruit maturity level of 25% and 50%higher than the other treatments. Combined treatment twiceof CaCl2 application on 90 and 120 daf with dosage of CaCl2100 kg ha' produces calcium content higher than the othertreatment and produce fruit texture, percentage of fruitdiseases and percentage of fruit bruised lower than othertreatments. Ethephon application had noeffect on calciumcontent but decreasing fruit texture, percentage of fruitdiseases and improved percentage offruit bruised. CaCl2 andethephonapplications didnot affect the total soluble solid,total acidity and vitamin C. .Keywords: CaCl2, ethephon, pineapple, fruit quality.